Ordinance No. 32: An Ordinance to Define Misdemeanors and Provide Penalty Therefor, and for Other Purposes, THE DAILY MORNING ALASKAN, Jun. 18, 1903, at 2 (Skagway, Alaska). §3 - (:unkn) unknown (General Publisher, 1903)
Prohibited brandishing any pistol, Bowie-knife, or other dangerous weapon in a threatening manner. Violators guilty of a misdemeanor punishable by fine of not more than two hundred dollars, or by imprisonment in jail not more than ninety days, or both.
--
Keywords: BRANDISHING